MORTGAGE FINANCE, MACROECONOMIC FACTORS AND HOUSING DEVELOPMENT IN NIGERIA - IBRAHIM, SHERIFF AKANJI; ABDURAUF, LUKMAN ADEBAYO-OKE; YUSUF, OLAMILEKAN QUADRI (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
Despite the critical role of housing as a component of economic growth and social stability, literatures has shown that housing development in Nigeria can be constrained by lack of long term financing, as well as macroeconomic factors. This study examines the intricate relationships between mortgage finance, housing development and the interactive effect of macroeconomic factors in Nigeria. This research employs data on housing delivery, mortgage finance and macroeconomic factors, sourced from the Central Bank of Nigeria (CBN) statistical bulletin and Federal Mortgage Bank of Nigeria (FMBN) annual audited report between 2005 to 2022. The research adopt an expos factor and experimental descriptive design. Pre-estimation test such as unit root test and Bound test were employed to test for stationarity and cointegration. Empirical analysis was conducted using the Autoregressive Distributed Lag (ARDL) model. Findings from this study revealed that mortgage loan interaction variable have a very weak positive effect on housing delivery in the long run, with a coefficient of 0.005230 (p-value; 0.0005), mortgage equity’s negative effect was also reduced in the long run, with a coefficient of -0.001611 (p-value; 0.0268). Mortgage interest rate was also found to have a reduced negative effect on housing delivery in the long run, with a coefficient of -0.005316 (p value; 0.0003). The research concludes that macroeconomic factors’ interaction with mortgage finance negatively affects changes in housing delivery. Consequently, the research recommends that policymakers implement holistic measures to stabilize the economy, while incentivizing mortgage lending to guarantees access to adequate and affordable housing for Nigeria’s growing population